Water table depth affects persistence and productivity of alfalfa in Central Argentina - Berhongaray, Gonzalo; Basanta, Maria; Jauregui, José Martín (Elsevier, 2019)
Alfalfa (Medicago sativa L.) is one of the most sown perennial legumes in the world. Water table depth can be both an opportunity and a threat for this crop. In this study we analyzed 20 years of field experimental data taken in Rafaela (Argentina) to study the impact of water table depth on productivity and persistence (plant cover; %) of alfalfa. The average 4-year cumulative above-ground productivity of different alfalfa genotypes was 51.8 Mg DM ha−1, with a mean final persistence of 54%. Water table depth explained 49% of the variance for productivity and 47% of that of persistence, and maximum productivity and persistence were observed when the water table depth was below 4 m depth. Our results indicated that there was a negative impact of shallow water tables on alfalfa production under rain-fed production conditions. These results could be used to inform management decisions and crop simulation models.